The Relationship Between Disciplinary Behavior and the Number of Memorized Students (RQS) of Air Tawar Barat, Padang City - Fitriani, Nora; Ismaniar, Ismaniar (Universitas Negeri Padang, 2024)
Memorizing the Al-Quran is a form of worship activity carried out by Muslims, but there are things that must be considered in memorizing the Al-Quran, namely intention, enthusiasm, obedience and the ability to manage time and other activities. Therefore, the implementation process requires discipline. However, what can be seen from the students at the Sakinah Al-Qur'an House is that the students still lack discipline in memorizing the Al-Qur'an. This research uses a quantitative correlational approach to collect and analyze data. Quantitative methods allow researchers to measure the relationship between disciplinary behavior and the amount of memorization of the Al-Qur'an. The data analysis technique used in this research uses the product moment formula with a significance level of 5% (=0.05). The results of this research obtained an rcount of 0.982. The rcount value is consulted with rtable at a 5% confidence level, namely 0.349 with N = 23. The rcount > rtable value means HO is rejected and Ha is accepted. This means that there is a significant relationship between disciplinary behavior and the amount of memorization by students at Sakinah Air Tawar Barat House, Padang City. So this research confirms that students who show good disciplinary behavior tend to have a higher amount of memorization, and vice versa. The implication of this research is the importance of strengthening discipline in the context of learning the Al-Qur'an, as well as the need for awareness of the importance of disciplined behavior to achieve optimal results in memorizing the Al-Qur'an.Keyword : Memorizing, discipline behavior, number of memorized, Qur'an House.